Pengaruh Kualitas Produk, Promosi dan Persepsi Harga Terhadap Keputusan Pembelian di Subway Margonda - Purba, Eva Yulyanti; Cyasmoro, Verry (Co-Creation : Jurnal Ilmiah Ekonomi Manajemen Akuntansi dan Bisnis, 2023)
This study aims to analyze the influence of Product Quality, Promotion and Price Perception on Purchasing Decisions at Subway Margonda using quantitative methods. The data in this study use primary data obtained by distributing questionnaires randomly to 100 Subway Margonda consumers with incidental sampling techniques. This study uses multiple linear regression analysis methods which include: validity and reliability tests, classical assumption tests, multiple regression analysis, determination coefficient analysis (R2), and hypothesis testing with t-tests and F-tests. The results of the study state that the product quality variable has a significant effect on purchasing decisions at Subway Margonda outlets. Also, the promotion and price perception variables have a positive and significant effect on purchasing decisions at Subway Margonda. It can be concluded that Subway Margonda has paid attention to the quality of its products and created ways to promote its products and price perceptions that are in accordance with the products offered.